DECAY OF EMERALD GREEN PIGMENTS ON EASEL PAINTINGS - Thanaa Ali Ali Abotaleb (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Emerald green is one of the pigment of its composition arsenic, copper It is usually used in coloring the areas of trees and clothing, the color by ageing and exposure to inappropriate environmental conditions (temperature, humidity, and ultraviolet) turn Dark brown color caused of changing chemical and structural composition of the paint layer, The changing in colored is not only from medium damage, but there are factors that play an auxiliary role with medium damage, The medium is decomposed and free fatty acids interact with metal ions in emerald green, which leads to the formation of mineral soap that leads to the instability of color particles , the loss of contact between of them it ,decompose it and forms a decomposition product of arsenic trioxide(As2O3), Which migrates on the surface and interacts with pollutants and discolored green. This article aims to study of the phenomenon of emerald green color change on an oil painting from the 19th century in Al Jazeera museum by the French artist Ad.Monticelli (1824-1886), using an examination by Micro scope Om , PLM ,analysis FTIR , XRD ,and SEM-EDX,. The Analytical XRD analysis showed that the archaeological color sample from emerald green, which has different mineral forms of arsenic damage, such as Copper hydrogen AsCuHO3, lead Arsenite [Pb2As2O5], and Clinoclase [Cu?AsO?(OH)?] is a mineral water arsenic copper and Arsenicsulfide As2S3 ,FTIR study showed the decomposition products of emerald green, as monocarboxylate, calcium oxalate salts, and arsenic trioxide [As2O3].